Rendimento da prova tuberculínica na investigação da Tuberculose Latente - (:unkn) unknown (Universidade Federal do Amazonas - Universidade Federal do Pará, 2012)
Pará is the fourth among states with the highest incidence, with an average of 3000 new cases annually. In 2010 were 47 cases/100000 in hab. and Belém is the third capital with more than 90 cases/100000 in habitants. To control this pandemic has been a great challenge, and the difficulties is the identification of carriers of LTBI to be treated, reducing the reservoir of M. tuberculosis in order to prevent future illnesses and break the transmission chain. This study aimed to evaluate the performance of the PT in the investigation of LTBI, the relationship between variables and to investigate factors related to potential gaps in the income. This is a cross-sectional, descriptive analytic approach, conducted at the Health Center of UEPA, Belém Pa, and reference to the performance of PT. The sample consisted of 328 people; the data were analyzed using chi-square tests, Fisher's exact test and multiple logistic regression, using the program Bio Stat 5.0 and SPSS 17.0, with a significance level of 0.05. Of the 328 participants, 196 (59.76%) had PT + 159 (81.12%) were identified with LTBI, with p-value of 0001, strengthening the importance of PT in the identification of LTBI. PT + was predominant among men (62.31%), aged 40-49 years (78.05%), normal (58.29%), TB contacts (68.37%), not immunosuppressive drug user (93.37%). Contact the variables TB, Chest X-ray unchanged, Age Group and Presence of LTBI were associated with the income of PT. So people who had contact with TB, showed no change in X-Ray, aged 00-04 years were respectively 71%, 55%, 33% much more likely to have PT + indicating LTBI. Although no association found between PT and immunosuppressive diseases in four of the diseases studied, the percentage was higher in PT +, diabetic, renal, CA and affected by other immunosuppressive diseases. Thus, we conclude that PT is still fundamental to any strategy for TB control because of its high predictive value in identifying LTBI and it’s available in the Public Health Services in Brazil. Its accuracy increases with the reduction of the probable causes of failures, but because of its weakness compared to immunosuppressed, it is necessary to undertake further studies to strengthen their strengths and discover new tests that could be apply this need and have applicability in Public Health.
Keywords: Tuberculose; Tuberculose Latente; Prova Tuberculínica; Tratamento da Tuberculose Latente; Diagnóstico da Tuberculose Latente; CIENCIAS DA SAUDE